Revisiting the Pharmakon - Marcel O'Gorman (Media Theory)
The concept of the techno-pharmakon, introduced by Plato in Phaedrus and later adopted by Jacques Derrida, reached the apex of its philosophical utility in the work of Bernard Stiegler. The simple idea that technology can either be a remedy or a poison, an idea central to Stiegler’s work, is an irresistible binary for media theorists. This essay begins with a critical reflection on that useful binary and on the white male legacy of the pharmakon itself, a legacy that I confess to have perpetuated. If technology can either cure or kill, it does not do so equally; rather, the pharmakon achieves radical variability depending on factors of race, gender, and ability. Put simply, this essay argues that the very same systemic power asymmetries that are responsible for our most pressing social problems are embedded in our technological systems. Moreover, these same power asymmetries haunt media theory itself, leading me to argue that the pharmakon needs to be troubled. I draw carefully on queer theory to recommend a path toward this disturbance of the power systems embedded in both technoculture and in media theory.